2016
DOI: 10.1007/s11906-015-0613-6
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, Diabetes, and Other Cardiovascular Risk Factors in Native Populations of South America

Abstract: Cardiovascular disease remains the leading cause of death in both developed and developing countries. In South America, the native population comprises a great number of different ethnic groups. The cardiovascular risk factors observed in these groups have proved similar to and even higher than those found in general non-native populations. Relatively recent epidemiologic information reveals that many native communities have healthy habits with low prevalence of risk factors such as hypertension and diabetes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
1
8
1
Order By: Relevance
“…These changes are comparable to those affecting Native Americans in the second half of the 20th century, during which important sociocultural changes led to a dramatic increase in chronic diseases (Young, 1997). In Latin America, other native populations also experienced similar changes, and they currently exhibit a high prevalence of obesity and, in some cases, type 2 diabetes mellitus (Ingaramo, 2016).…”
Section: Discussionmentioning
confidence: 75%
“…These changes are comparable to those affecting Native Americans in the second half of the 20th century, during which important sociocultural changes led to a dramatic increase in chronic diseases (Young, 1997). In Latin America, other native populations also experienced similar changes, and they currently exhibit a high prevalence of obesity and, in some cases, type 2 diabetes mellitus (Ingaramo, 2016).…”
Section: Discussionmentioning
confidence: 75%
“…Recent studies in human and animal models have suggested that validating ICD coding with imaging data could make a strong study [69,73,80,81], as these studies address the issue of possible coding errors. Second, the obesity-DDD association from this study should be interpreted with caution, since it does not reject the “reverse causality” hypothesis (the spinal conditions could increase the risk for obesity as juvenile disc degeneration was strongly associated with diminished physical functioning [6] and diminished physical functioning could mean less energy expenditure). Moreover, with available evidence suggesting a likely relationship between increased BMI and a variety of pain conditions, the question remains as to whether the link we identified here was specific to spinal conditions [82].…”
Section: Discussionmentioning
confidence: 99%
“…Ogden et al [3] reported that the prevalence of obesity in the U.S. was 36.5% among adults and 17% among children and youth during 2011–2014. Obesity is associated with many prevalent conditions including prostate disease [4], cardiovascular diseases [5], diabetes [6], and osteoarthritis [7,8]. A number of studies have found a consistent association between obesity and low back pain (LBP) [9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerosis and associated cardiovascular diseases (CVD) represent the major cause of death and comorbidities in Western and developing countries [ 1 , 2 ]. The Global Burden of Disease Study estimated that about 32% of all deaths worldwide in 2013 were caused by CVD, with about 80% of these deaths occurring in low-and middle-income countries [ 3 ].…”
Section: Introductionmentioning
confidence: 99%